2009
DOI: 10.1007/s00405-009-1154-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional results of 394 bilateral stapedotomies evaluated with the Glasgow Benefit Plot

Abstract: This study aimed to evaluate the results of 394 bilateral stapedotomies according to the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) guidelines and with the Glasgow Benefit Plot (GBP) and also analyze the benefit of a second-ear stapedotomy in achievement of normal and symmetrical hearing using retrospective chart review. The charts of 1,369 stapedotomies performed by senior author (J.H.) from 1991 to 2006 were reviewed. Results of 394 bilateral stapedotomies were included. The hearing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…While the second ear surgery does not show a significant increase in ULL, the participants’ subjective statements substantiate the benefit of second ear surgery. Similar phenomena where greatest benefit occurs after the first ear surgery has been observed in subjects who underwent bilateral stapedotomies (26). While we were not able to perform statistical testing because of our small sample size, a positive trend was noted with improvement of the ULLs when analyzing first ear and second ear surgeries.…”
Section: Discussionsupporting
confidence: 70%
“…While the second ear surgery does not show a significant increase in ULL, the participants’ subjective statements substantiate the benefit of second ear surgery. Similar phenomena where greatest benefit occurs after the first ear surgery has been observed in subjects who underwent bilateral stapedotomies (26). While we were not able to perform statistical testing because of our small sample size, a positive trend was noted with improvement of the ULLs when analyzing first ear and second ear surgeries.…”
Section: Discussionsupporting
confidence: 70%
“…The Belfast rule of thumb is empirically defined, but more commonly used is its graphic derivative (23), the Glasgow Benefit Plot (14,17,19,20,23): normal hearing is a hearing impairment of 30 dB or lesser and symmetrical hearing as interaural difference of 10 dB or lesser. Using this stricter definition of symmetrical hearing in this study would make the small symmetrical hearing group even smaller and further impair statistical comparison among The overall score is the mean score of the 4 listening situations.…”
Section: Discussionmentioning
confidence: 99%
“…The hearing outcome in bilateral otosclerosis has been documented by fewer studies only. 6,7 Database research in the past shows varying results with some studies showing second ear surgery are less successful compared to the first while few other studies have shown satisfactory results in both ears. [16][17][18][19] Our study aimed at providing evidencebased recommendation rather than just an opinion and helps both clinicians and patients getting the valuable based reference data.…”
Section: Discussionmentioning
confidence: 99%
“…Today with a well experienced hands more than 95% of optimal results can be achieved with a low incidence of complications. [5][6][7] In recent years, there has been an increasing interest in evaluating the benefits and outcomes of second ear surgeries in bilateral stapedectomies. Considering the patient for operating the second ear it is still a dilemma for many surgeons as the risk of immediate or permanent sensorineural hearing loss (SNHL) and vestibular dysfunction exists while exposing for the second time.…”
mentioning
confidence: 99%
See 1 more Smart Citation